William Morris and the atomic. (1st April 2017) - Mabb, David
A Provisional Memorial to Nuclear Disarmament was made in response to a visit to HMS Courageous, a decommissioned nuclear powered submarine furnished with William Morris 'Rose' fabrics. The Ministry of Defence commissioned the fabric for its nuclear submarines for over 30 years, from the 1960s through to the late 1990s, including the Vanguard Class nuclear-powered ballistic missile submarines that are armed with Trident nuclear-armed missiles. In the black and white photographs that follow, each of the fourteen works is represented twice, from the front and the back. The works consist of old projection screens in which the white screen fabric has been removed and replaced. The fronts of the screens are mostly painted black, with some Morris patterns. On the back of the screens William Morris patterned fabrics have been painted with anti-nuclear slogans and signs.